2013
DOI: 10.1111/aor.12071
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oxygenated Machine Perfusion System for Preservation of the Liver

Abstract: Machine perfusion (MP) is a potential method to increase the donor pool for organ transplantation. However, MP systems for liver grafts remain difficult to use because of organ-specific demands. Our aim was to test a novel, portable MP system for hypothermic preservation of the liver. A portable, pressure-regulated, oxygenated MP system designed for kidney preservation was adapted to perfuse liver grafts via the portal vein (PV). Three porcine livers underwent 20 h of hypothermic perfusion using Belzer MP solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…Importantly, the rate of oxygen consumption during HMP decreases rapidly during the first hour and ceases after 90 min at a low baseline level because of downregulation of mitochondrial respiration despite increasing ADP and sufficient levels of substrates (oxygen and electron donors) [15, 23, 24]. Accordingly, during hypothermic oxygenated liver perfusion, mitochondria switch from a high-flux electron transfer stage at the beginning of machine perfusion to a low-flux electron transfer stage during approximately 60-90 min of perfusion.…”
Section: Perfusion Conditionsmentioning
confidence: 99%
“…Importantly, the rate of oxygen consumption during HMP decreases rapidly during the first hour and ceases after 90 min at a low baseline level because of downregulation of mitochondrial respiration despite increasing ADP and sufficient levels of substrates (oxygen and electron donors) [15, 23, 24]. Accordingly, during hypothermic oxygenated liver perfusion, mitochondria switch from a high-flux electron transfer stage at the beginning of machine perfusion to a low-flux electron transfer stage during approximately 60-90 min of perfusion.…”
Section: Perfusion Conditionsmentioning
confidence: 99%
“…This study showed that continuous perfusion via the portal vein can be maintained with an oxygen-driven pump system without notable preservation damage of the organ. 17 In a porcine liver transplant model, Vekemans and associates studied SCS-discarded human liver grafts to either 4 hours of HMP or an additional 4 hours of SCS. All livers were then warm reperfused to mimic ischemia-reperfusion injury ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to NMP settings, HMP settings are by definition not particularly physiologic, with perfusate temperature most commonly defined as 4°C. Many porcine HMP studies used kidney perfusion solution (KPS‐1), also known as UW solution of Belzer MP . Bessems et al was unique in comparing Celsior perfusate versus Polysol with the result that Celsior solution was more damaging than Polysol, increasing AST/ALT and intravascular resistance to a greater extent .…”
Section: Hypothermic Machine Perfusion Settingsmentioning
confidence: 99%